2015
DOI: 10.1002/cbdv.201400084
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Neolitsea of Lauraceae: A Phytochemical and Biological Progress

Abstract: As one of the biggest genera in Lauraceae, Neolitsea owns a great application potential in industrial and traditional medical fields. Modern phytochemical and biological investigations revealed its structural diversity and diverse activities. This review summarizes the most recent progress on this regards, hopefully to provide a reference for full use and development of the Neolitsea resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The 3J coupling appears between (H-2) and (H-3) in the COSY spectrum, as well as between the (H-5) and (H-6), confirming the position of the protons in the molecule, in addition to comparison with literature data (Reynolds et al, 1986). Lupeol was isolated from many plants in the Lauraceae such as Neolitsea sericea (Cao et al, 2015), Beilschmiedia glabra (Lenta et al, 2015) and B. erythrophloia (Salleh and Ahmad, 2017). In addition, it was isolated from other families such as Ficus pseudopalma Blanco (Santiago and Mayor, 2014) and Scapium macropodum (Al Muqarrabun et al, 2014).…”
Section: Resultssupporting
confidence: 76%
“…The 3J coupling appears between (H-2) and (H-3) in the COSY spectrum, as well as between the (H-5) and (H-6), confirming the position of the protons in the molecule, in addition to comparison with literature data (Reynolds et al, 1986). Lupeol was isolated from many plants in the Lauraceae such as Neolitsea sericea (Cao et al, 2015), Beilschmiedia glabra (Lenta et al, 2015) and B. erythrophloia (Salleh and Ahmad, 2017). In addition, it was isolated from other families such as Ficus pseudopalma Blanco (Santiago and Mayor, 2014) and Scapium macropodum (Al Muqarrabun et al, 2014).…”
Section: Resultssupporting
confidence: 76%
“…In Taiwan, there are 12 Neolitsea species and four of them, including N. acuminatissima , N. daibuensis , N. hiiranensis , and N. parvigemma , are endemic [19]. Recent studies on the diversity of phytochemical structures and bioactivities revealed the application potential of Neolitsea plants in industrial and medical fields [20, 21]. Parts of Neolitsea plants have been used in folk medicine for long periods of time in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…The roots of N. zeylanica have been shown to relieve rheumatic arthralgia [22]. Studies on the chemistry and pharmacology of Neolitsea species have led to the isolation and identification of more than 150 compounds including alkaloids, terpenoids, sterols, steroids and their derivatives, flavonoids, essential oils, and fatty acids with diverse activities [21, 23]. The essential oils of N. pallens exhibited antioxidant and antibacterial activities [24].…”
Section: Introductionmentioning
confidence: 99%
“…Neolitsea is a genus of evergreen shrubs and small trees belonging to the Laurel family, Lauraceae. Approximately 100 species of the genus are found mainly in tropical regions of Asia [1] and some species are distributed in America [2], Australia and Malaysia [3]. A number of Neolitsea species, such as N. zeylanica [4] and N. aurata [5], are used traditionally for treating various illnesses.…”
mentioning
confidence: 99%